Lectin inspired polymers based on the dipeptide Ser-Asp for glycopeptide enrichment. Issue 21 (1st October 2018) - Zhang, B.; Yu, R. Z.; Yu, Y. H.; Peng, C.; Xie, R.; Zhang, Y.; Chen, J. Y.
Abstract : Lectin inspired polymers polySD-SiO2 were prepared and applied to the high-efficiency enrichment of glycopeptides. Abstract : Lectin inspired polymers were prepared through modification of silica microspheres with Ser-Asp (SD). This functional polymer showed distinct adsorption and retention towards different disaccharides and demonstrated high-efficiency enrichment of glycopeptides.